ANALISIS PERHITUNGAN, PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 DI PT. SURABAYA INN BERKARYA - AYU PUSPITA, DIAN Ayu (Jurnal Akuntansi AKUNESA, 2013)
This study discusses the calculation, withholding, depositing and reporting incometax under Article 21 are carried out by PT. Surabaya Inn Berkarya. Discussion about thesuitability of withholding tax with tax provisions. Methods of research using descriptivemethod. Data collection techniques using the research literature and documentation.Analysis using qualitative descriptive analysis.The results of this study is the suitability of thecalculation, deduction and remittance of income tax under Article 21 in the PT. Surabaya InnBerkarya with tax laws. In the reporting has not been seen in the corresponding receipts fromthe Tax Office Primary Genteng.Keywords: Calculation, Withholding, Remittance, Reporting, Income Tax Article 21